1983
DOI: 10.1136/jnnp.46.10.963
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of post-traumatic choreo-athetosis with sodium valproate.

Abstract: Treatment of post-traumatic choreoathetosis with sodium valproate Sir: We report a study which establishes the efficacy of sodium valproate in the treatment of post-traumatic choreoathetosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Despite rare reports of chorea secondary to its use, valproate can improve chorea, such as post-traumatic choreoathetosis [136], 'senile' chorea [137], hemiballismus of vascular origin [138], and particularly Sydenham's chorea [139], as confirmed by small series showing sustained and dramatic effects within a few days from treatment initiation [140].…”
Section: Valproatementioning
confidence: 99%
“…Despite rare reports of chorea secondary to its use, valproate can improve chorea, such as post-traumatic choreoathetosis [136], 'senile' chorea [137], hemiballismus of vascular origin [138], and particularly Sydenham's chorea [139], as confirmed by small series showing sustained and dramatic effects within a few days from treatment initiation [140].…”
Section: Valproatementioning
confidence: 99%
“…46 In the following years, several cases and case series reporting efficacy of valproate for chorea related to various etiologies were published. [47][48][49][50][51][52][53][54][55] In a retrospective comparison study by Pena et al, 29 valproic acid was found to be more effective than carbamazepine and haloperidol. Genel et al 56 prospectively compared valproic acid and carbamazepine and reported that they are equally effective and safe.…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…The anticonvulsant sodium valproate has been used effectively to treat Sydenham chorea in children 16 , 17 as well as the choreiform movements seen in other disorders such as posttraumatic choreoathetosis, 18 kinesiogenic familial paroxysmal choreoathetosis, 19 hemibal‐lismus, 20 , 21 and myoclonus 22 , 23 . Sodium valproate has not been effective in the treatment of Huntington disease 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%